2008
DOI: 10.3200/jrlp.142.5.517-532
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Load and Task Condition in Event- and Time-Based Prospective Memory: An Experimental Investigation

Abstract: Prospective memory is memory for the realization of delayed intention. Researchers distinguish 2 kinds of prospective memory: event- and time-based (G. O. Einstein & M. A. McDaniel, 1990). Taking that distinction into account, the present authors explored participants' comparative performance under event- and time-based tasks. In an experimental study of 80 participants, the authors investigated the roles of cognitive load and task condition in prospective memory. Cognitive load (low vs. high) and task conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 21 publications
4
35
2
Order By: Relevance
“…By contrast, it could be argued that older adults do not have sufficient attentional resources to respect these parallel task constraints as well as to take the opportunity to watch the clock to manage their time response. This explanation is consistent with the observation of Khan et al (2008) that the frequency of clock checking by young adults in a prospective memory task was lower under a high than a low cognitive load condition. In our study, although our ongoing task involved a low cognitive load, the older adults behaved as if the clock was an additional load rather than an aid.…”
Section: Strategic Clock Monitoringsupporting
confidence: 89%
See 1 more Smart Citation
“…By contrast, it could be argued that older adults do not have sufficient attentional resources to respect these parallel task constraints as well as to take the opportunity to watch the clock to manage their time response. This explanation is consistent with the observation of Khan et al (2008) that the frequency of clock checking by young adults in a prospective memory task was lower under a high than a low cognitive load condition. In our study, although our ongoing task involved a low cognitive load, the older adults behaved as if the clock was an additional load rather than an aid.…”
Section: Strategic Clock Monitoringsupporting
confidence: 89%
“…Khan, Sharma, and Dixit (2008) showed that inaccurate responses on TBPM tasks were associated with a low monitoring rate during the last stage of the monitoring period. In order to perform a TBPM task efficiently, people must be able to interrupt the ongoing activity deliberately to check whether sufficient time has elapsed to initiate the intended action (Harris & Wilkins, 1982).…”
Section: Age Effects On Tbpm: the Issue Of Temporal Strategiesmentioning
confidence: 98%
“…Indeed, young participants reported both automatic retrieval and constant monitoring in the same proportion (50/50) for EBPM while the majority of them reported a different strategy in TBPM. Indeed, 70% reported a periodic checking of time, including the classical "J-shaped" curve strategy (see for example Khan et al 2008;Occhionero et al 2010), and only 30% reported sustained or constant clock monitoring. By contrast, the proportion reporting having relied on a constant checking of the clock in TBPM is higher in older participants (50%; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…First, the difficulty of the ongoing task can be varied (e.g., Marsh et al, 2002; McNerney and West, 2007; Khan et al, 2008; West et al, 2011). Second, an additional ongoing task can be added, thus requiring divided attention (e.g., Kliegel et al, 2001, 2004; Khan et al, 2008). Third, loads can be manipulated by adding and varying the difficulty of a third ongoing task (Wang et al, 2006).…”
Section: Importance Of Intentionsmentioning
confidence: 99%